2020
DOI: 10.1124/dmd.120.000033
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cryopreserved Human Intestinal Mucosa and Cryopreserved Human Enterocytes in the Evaluation of Herb-Drug Interactions: Evaluation of CYP3A Inhibitory Potential of Grapefruit Juice and Commercial Formulations of Twenty-Nine Herbal Supplements

Abstract: Commercial formulations of 29 commonly used herbal supplements (HS) and grapefruit juice were evaluated for drug interaction potential via quantification of their CYP3A inhibitory potential in two in vitro experimental models of human small intestine, cryopreserved human intestinal mucosa (CHIM) and cryopreserved human enterocytes (CHE). Two CYP3A substrates were used-in the studies with CHIM, CYP3A activity was quantified via LC/MS-MS quantification of midazolam 1'-hydroxylation while in CHE, luciferin IPA me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The current research pertaining to G. biloba flavonoids and CYP450 enzymes is mainly focused on CYP3A4, which is one of the key enzymes of drug metabolism and plays a pivotal role in the metabolism of more than 50% of the drugs on the market. It’s intriguing that many studies have shown that ginkgolides have the effect of activating CYP3A4 enzyme system, while G. biloba extract and flavonoids have inhibitory effects against CYP3A4 enzyme ( 62 , 65 , 66 ). However, one study has also shown that kaempferol has a weak effect on CYP3A4 enzyme ( 72 ).…”
Section: Metabolism Of Flavonoids Of Ginkgo Biloba ...mentioning
confidence: 99%
“…The current research pertaining to G. biloba flavonoids and CYP450 enzymes is mainly focused on CYP3A4, which is one of the key enzymes of drug metabolism and plays a pivotal role in the metabolism of more than 50% of the drugs on the market. It’s intriguing that many studies have shown that ginkgolides have the effect of activating CYP3A4 enzyme system, while G. biloba extract and flavonoids have inhibitory effects against CYP3A4 enzyme ( 62 , 65 , 66 ). However, one study has also shown that kaempferol has a weak effect on CYP3A4 enzyme ( 72 ).…”
Section: Metabolism Of Flavonoids Of Ginkgo Biloba ...mentioning
confidence: 99%
“…59 CHIM has been applied towards the evaluation of DDI potential of commercial formulations of herbal supplements, identifying green tea extract, St. John's wort, valerian root, horehound, and grapefruit juice as having potent CYP3A inhibition/induction potentials, and suggesting potential for herb-drug interaction with orally administered drugs that are Accepted Article CYP3A substrates. 60 CHIM as an experimental tool for the evaluation of intestinal drug toxicity is illustrated by dose-dependent cytotoxicity of the non-steroidal anti-inflammatory drugs (NSAIDs) acetaminophen and naproxen, with naproxen exhibiting a higher enterotoxicity than acetaminophen as in humans in vivo. 56 The robust drug-metabolizing enzyme activity is a major advantage of CHIM over crypt cell/stem cell-derived and cell line-based in vitro enteric models.…”
Section: Novel In Vitro Enteric Models For Ddis and Safety Evaluationmentioning
confidence: 99%
“…CHIM is found to be a useful experimental model for the evaluation of first‐pass intestinal metabolism of orally administered drugs for the estimation of the fraction escaping gut metabolism, especially for moderately and rapidly metabolized drugs 59 . CHIM has been applied toward the evaluation of DDI potential of commercial formulations of herbal supplements, identifying green tea extract, St. John’s wort, valerian root, horehound, and grapefruit juice as having potent CYP3A inhibition/induction potentials, and suggesting potential for herb‐drug interaction with orally administered drugs that are CYP3A substrates 60 . CHIM as an experimental tool for the evaluation of intestinal drug toxicity is illustrated by dose‐dependent cytotoxicity of the nonsteroidal anti‐inflammatory drugs acetaminophen and naproxen, with naproxen exhibiting a higher enterotoxicity than acetaminophen as in humans in vivo 56 .…”
Section: D In Vitro Intestine Modelsmentioning
confidence: 99%
“…Can delay or reduce drug absorption; 1 h time-lag between application [69] Minerals, vitamins, drugs obstruction risk with drugs that inhibit peristaltic movements Opioids Garlic Inhibition of CYP2E1 [70], but not 2D6 and 3A4 [70,71]; induces pGP [72] Cyclosporine, tacrolimus Elevated bleeding risk due to platelet inhibition suspected [53,73]; contradicting clinical data [73,74] Monitor patients on anticoagulants when starting/ending garlic preparations; caution with antiplatelet drugs (NSAIDs, especially ASA) [75][76][77]; cases of interactions with dabigatran (pGP) [78], phenprocoumon (CYP2C9) [79], and crizotinib (CYP3A4, 2C9; pGP) [80]; no effect in a clinical study with warfarin (CYP2C9) [81]; elevated tacrolimus AUC in rats [82] CYP2C9, 3A4 and pGP substrates with narrow therapeutic window, such as cyclosporine, tacrolimus Inhibits platelet aggregation in vitro [83] Caution with anticoagulant and platelet-aggregation inhibiting drugs (NSAIDs) Inhibits UDP1A6 in vitro [86]; CYP3A4 and 2C9 inhibition suspected, but no relevant influence in small clinical studies [87][88][89][90][91]; case report of warfarin interaction, probably due to CYP2C9 inhibition [92] Caution with CYP3A4 and 2C9 substrates with small therapeutic windows (such as cyclosporine)…”
Section: Flaxseedmentioning
confidence: 99%